I don't understand how to get from this:

$\displaystyle S = 2\pi \int \frac{x^3}{3} \sqrt{1+x^4} dx$ [0,3]

to this:

$\displaystyle

= \frac{\pi}{6} \int (1+x^4)^{1/2}(4x^3) dx$ [0,3]

The only thing I understand really is rewriting the square root.

Printable View

- Feb 7th 2009, 04:29 PMsaiyanmx89Arc Length
I don't understand how to get from this:

$\displaystyle S = 2\pi \int \frac{x^3}{3} \sqrt{1+x^4} dx$ [0,3]

to this:

$\displaystyle

= \frac{\pi}{6} \int (1+x^4)^{1/2}(4x^3) dx$ [0,3]

The only thing I understand really is rewriting the square root. - Feb 7th 2009, 04:36 PMoswaldo
They are the same thing can't you see. It's just reaarangements of coefficients.. And 2/3 = 4/6.

-O